Food security in Ukraine: Indicative analysis of problems and perspectives of Their Solution - Lyudmila Shymanovska-Dianych; Nazariy Popadynets; Svitlana Hrynkevych; Svitlana Shults; Тymur Ishcheikin; Roma Staryk (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2021)
The paper aims to reveal the advantages of the food behavior of the Ukrainian population and the problems of forming of domestic consumer demand in the context of indicators of the country's socio-economic development. Obtained results characterize the food security condition of Ukraine. Maintenance of food independence in every country is and will always be a very urgent matter from the viewpoint of the constant need for proper addressing the primitive necessities of the population for food by the state. The advantages and problems of food security organization in Ukraine are characterized based on the assessment of its Global Food Security Index rankings and indicators of the country’s development level. Growing indicators of food accessibility and quality/security and improving the level of consumption of certain food groups and nutrition standards, in particular in terms of their dietary diversity are the indisputable advantages of Ukraine. Indicative analysis of food security policy implementation in Ukraine has shown that the dynamics of GDP, trade volumes, production scales, purchase power and inflation dynamics impact the consumer capacities of the Ukrainian population. The paper substantiates that the perspectives of food security in Ukraine depend on the support of own production, the stability of food provision, growing quality of products, adequate management of national food reserves, rational pricing and development of trade and transport infrastructure. The paper aims to reveal the advantages of the food behavior of the Ukrainian population and the problems of forming domestic consumer demand in the context of indicators of the country’s socio-economic development. Obtained results characterize the food security condition of Ukraine.